Accelerating digital trade in Latin America and the Caribbean - Kati Suominen (Inter-American Development Bank (IDB), 2017)
The Internet roared to the scene in Latin America and it is transforming the way Latin Americans interact, shop, bank, and spend their time. The Internet is changing regional consumption patterns, the landscape of regional companies, and the region's economic prospects. Disruptive digital technologies riding on the web -cloud-based services, e-commerce, 3D printing, Internet of Things, and so on- are empowering LAC companies of all sizes to dramatically cut costs, improve customer service, and create brand new products and services. The region is also home to innovative digital companies run by intrepid entrepreneurs, some of whom have accessed significant investments from Silicon Valley and grown into some of the leading digital companies. The Internet, in short, has opened tremendous new opportunities for LAC economies to become more productive, expand opportunities for entrepreneurship, and drive inclusive economic growth.
Keywords: O39; 330; digital trade; internet; SME; ConnectAmericas